Analysis of Teachers' Needs in Renewable Energy Learning Programs Using SSI Integrated with PjBL-STEM to Enhance Collaborative Problem-Solving and Entrepreneurial Skills - Sri Rahayu; Abdurrahman; Kartini Herlina; Agus Suyatna; Chandra Ertikanto (Jurnal Penelitian Pendidikan IPA, 2025)
This preliminary study explores the needs of teachers and students in physics learning, focusing on renewable energy topics. Using a survey method, data were collected from 24 high school physics teachers in Lampung Province via Google Forms. The findings were analyzed to identify educational gaps and propose solutions. Results reveal a pressing need for learning programs that enhance Collaborative Problem-Solving and Entrepreneurial Skills. While 83.30% of teachers reported integrating Project-Based Learning STEM (PjBL-STEM) into their teaching, only 23.50% of worksheets used were PjBL-STEM-based, and just 26.70% were self-created. Teachers faced challenges such as limited time and difficulty initiating development. Additionally, only 54.20% of teachers were familiar with the Sustainable Development Goals (SDGs). The study also highlights gaps in skill assessment, with 75% of teachers not evaluating Collaborative Problem-Solving Skills and 87.50% not assessing Entrepreneurial Skills. Despite using teaching media and worksheets, these gaps suggest a need for more robust tools and methods.The findings underscore the importance of developing renewable energy learning programs integrated with PjBL-STEM. Such programs can address existing challenges, promote SDG awareness, and equip students with critical skills for collaboration and entrepreneurship in the context of physics education.